An overview of theoretical analysis method for composite repaired pipelines - Deng, Meilin L.; Yang, Jing; Bao, Chao; Norhazilan, Md Noor; Lim, Kar Sing (Bentham Open, 2024)
Pipelines are an important way of transportation for gas, oil and other petroleum products, and they are typically exposed to a harsh environment, leading to corrosion defects, cracks, leakage, dents and so on. A composite repair system is a favourable repair system for defective pipelines owing to its high strength, lightweight, cost-effectiveness, elimination of explosion and so on. Considerable research has been carried out on the composite repaired pipelines. However, there are still many issues and challenges to overcome in order to improve the existing repair designs. Therefore, this paper aims to review the theoretical analysis method for pressurized composite repaired pipelines. A better understanding of the mechanisms of stress distribution will benefit the development of composite repaired pipelines. They are mainly summarized into three models, namely the one-layer model, two-layer model, and three-layer model, which are all based on the thin-walled theory and the Lame approach. Both the advantages and disadvantages of these theoretical models are highlighted. Finally, in the conclusion section, the current research gap and future scopes of study in the theoretical analysis are also presented to provide insight into a more effective design philosophy for composite repaired pipelines.